Carbon-Based Materials for Supercapacitors: Recent Progress, Challenges and Barriers - Abdul Ghani Olabi; Qaisar Abbas; Mohammad Ali Abdelkareem; Abdul Hai Alami; Mojtaba Mirzaeian; Enas Taha Sayed (Batteries, 2022)
Swift developments in electronic devices and future transportation/energy production directions have forced researchers to develop new and contemporary devices with higher power capacities, extended cycle lives, and superior energy densities. Supercapacitors are promising devices with excellent power densities and exceptionally long cycle lives. However, commercially available supercapacitors, which commonly use high-surface-area carbon-based electrodes and organic solutions as electrolytes, suffer from inferior energy densities due to the limited accessibility of surface area and constrained operating potential window of electrolytes. To address the issue of inferior energy densities, new high-capacity electrode materials and new/state-of-the-art electrolytes, such as ionic liquids, gel polymers, or even solid-state electrolytes, have been developed and evaluated vigorously in recent years. In this brief review, different types of supercapacitors, according to their charge storage mechanisms, have been discussed in detail. Since carbon-based active materials are the key focus of this review, synthesis parameters, such as carbonisation, activation, and functionalisation, which can impact a material’s physiochemical characteristics, ultimately affecting the performance of supercapacitors, are also discussed. Finally, the synthesis and applications of different carbon-based materials, i.e., carbon nanotubes, graphene, and activated carbon, have been reviewed, followed by conclusions and outlook.